Tillage practices on soil penetration resistance, soil infiltration, percolation and yield of rice (Oryza sativa) in rice-based cropping system - SUBRAHMANIYAN, K; RAJAVEL, M; VEERAMANI, P; PARTHIPAN, T (The Indian Journal of Agricultural Sciences, 2024)
The experiment was conducted during 2019–23 at Tamil Nadu Rice Research Institute (Tamil Nadu Agricultural University, Coimbatore), Aduthurai, Tamil Nadu to analyse the effect of conservation tillage methods on bulk density, soil penetration resistance and soil infiltration rate of clay soil and rice yield in rice-based cropping system. Experiment consisted of three tillage practices, viz. conventional tillage/puddling (CT); zero tillage (ZT); and minimal tillage/dry ploughing (MT) and two rice (Oryza sativa L.) cultivars (ADT 43 and CORH 3), replicated four times. The result of the study revealed that the bulk density was significantly lower with zero tillage due to presence of crop residues and addition of organic matter. The mean infiltration rate under zero tillage was 0.16 cm/h as compared to puddling (0.14 cm/h) and dry ploughing (0.20 cm/h). The study further showed that the mean soil percolation rate was significantly altered by the tillage methods and soil percolation rate was 0.12 cm/h in zero tillage as compared to puddling (0.10 cm/h) and dry ploughing (0.16 cm/h). In contrary to the other physical properties, the soil penetration resistance was in the order of dry ploughing>zero tillage>puddling. The mean soil penetration resistance under zero tillage was reduced from 690–500 Kpa, 740–600 Kpa and 760–620 Kpa respectively at 0–5, 5–10 and 10–15 cm depth as compared to puddling. The results further indicated that the yield parameters and rice did not differ among the different tillage practices.